Activation of ryanodine-sensitive calcium store drives pseudo-allergic dermatitis via Mas-related G protein-coupled receptor X2 in mast cells - Wang, Zhao; Zhao, Xi; Zhou, Hongmei; Che, Delu; Du, Xiaojie; Ye, Dan; Zeng, Weihui; Geng, Songmei (Frontiers in Immunology, 2023)
Mast cell (MC) activation is implicated in the pathogenesis of multiple immunodysregulatory skin disorders. Activation of IgE-independent pseudo-allergic route has been recently found to be mainly mediated via Mas-Related G Protein-Coupled Receptor X2 (MRGPRX2). Ryanodine receptor (RYR) regulates intracellular calcium liberation. Calcium mobilization is critical in the regulation of MC functional programs. However, the role of RYR in MRGPRX2-mediated pseudo-allergic skin reaction has not been fully addressed. To study the role of RYR in vivo, we established a murine skin pseudo-allergic reaction model. RYR inhibitor attenuated MRGPRX2 ligand substance P (SP)-induced vascular permeability and neutrophil recruitment. Then we confirmed the role of RYR in an MC line (LAD2 cells) and primary human skin-derived MCs. In LAD2 cells, RYR inhibitor pretreatment dampened MC degranulation (detected by β-hexosaminidase release), calcium mobilization, IL-13, TNF-α, CCL-1, and CCL-2 mRNA and protein expression activated by MRGPRX2 ligands, namely compound 48/80 (c48/80) and SP. Moreover, the inhibition effect of c48/80 by RYR inhibitor was verified in skin MCs. After the confirmation of RYR2 and RYR3 expression, the isoforms were silenced by siRNA-mediated knockdown. MRGPRX2-induced LAD2 cell exocytosis and cytokine generation were substantially inhibited by RYR3 knockdown, while RYR2 had less contribution. Collectively, our finding suggests that RYR activation contributes to MRGPRX2-triggered pseudo-allergic dermatitis, and provided a potential approach for MRGPRX2-mediated disorders.